ANALISIS DE LAS LIMITACIONES EN EL SISTEMA DE BODEGA DE LA UNIDAD EDUCATIVA EUGENIO ESPEJO. - Ulpo Chimbo, Lilia Maribel (2018)
At present the Educational Institution "Eugenio Espejo" has shortcomings to conduct a large amount of information, with the passage of time has allowed the appropriate management of information, with this management will lead to a correct management that is to say we will have the most clear information and secure with this we can safely have a very safe and efficient information for this institution. The Educational Institution "Eugenio Espejo" has made thousands of efforts to obtain a Control Software and Assets that can be managed to the needs that the user requires, the Software will have computer tools that will help the manager or the user obtain the secure information to improve the account performance process of the Asset Management and Control System. Currently the Software that has the Educational Institution "Eugenio Espejo" in the city of Babahoyo was obtained by the needs by at that time the Department of Warehouse had a Software with thousands of problems and always had certain limitations.